2016
DOI: 10.1002/adfm.201504705
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Saturated Contact Angle in Electrowetting‐on‐Dielectrics by Controlling the Charge Trapping at Liquid–Solid Interfaces

Abstract: Contact angle saturation in electrowetting‐on‐dielectrics (EWOD) has restricted the tuning range of the wettability of a solid surface, which has generally limited the performances of EWOD devices such as digital microfluidics, lab‐on‐chip, electronic displays, and so forth. Here, a method is proposed for decreasing the saturated contact angle by controlling the behavior of charge trapping at the liquid–solid interface. An unexpected phenomenon is uncovered: for a short time the contact angle reaches smaller v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 34 publications
4
71
0
Order By: Relevance
“…Under a negative electrical potential, the dodecyl chain tails will be positively charged ( Fig. 3B) (36). Therefore, the positively charged dodecyl chain tails will move toward the negatively charged silver porous membrane, achieving orientation change of the dodecyl chain tails (Fig.…”
Section: Mechanism Of the Wettability Transitionmentioning
confidence: 99%
“…Under a negative electrical potential, the dodecyl chain tails will be positively charged ( Fig. 3B) (36). Therefore, the positively charged dodecyl chain tails will move toward the negatively charged silver porous membrane, achieving orientation change of the dodecyl chain tails (Fig.…”
Section: Mechanism Of the Wettability Transitionmentioning
confidence: 99%
“…3(b need time to migrate in reverse. Before the charges finish migrating, the reverse electric field and the external electric field form a short-term codirectional superposition, making the electric field stronger than in the saturated state [53]. Under a certain frequency of reversing, the superposition electric field can maintain a stable value that is higher than the pristine saturation voltage, so the contour curvature formed under the square wave voltage condition is larger.…”
Section: Ray Tracing Simulationsmentioning
confidence: 99%
“…This negative behavior of EWD is called “backflow” which may lead to the stability degradation of EWD. Some scholars have found that charge trapping is one reason for backflow. Fig .…”
Section: Electro‐optic Response Characteristics Of Ewdmentioning
confidence: 99%
“…This negative behavior of EWD is called "backflow" which may lead to the stability degradation of EWD. Some scholars have found that charge trapping is one reason for backflow 15,16 . Fig.3 illustrates the charge trapping phenomenon of EWD by plotting reflectivity as a function of time in red dotted line.…”
Section: Backflowmentioning
confidence: 99%